2011
DOI: 10.1007/s11244-011-9751-5
|View full text |Cite
|
Sign up to set email alerts
|

In Situ FT-IR Mechanistic Investigations of the Zeolite Catalyzed Methylation of Benzene with Methanol: H-ZSM-5 versus H-beta

Abstract: The methylation of aromatics is a reaction step that occurs in several petrochemical processes. Here, we have investigated the methylation of benzene by methanol over H-ZSM-5 and H-beta catalysts by conducting kinetic measurements and in situ FT-IR spectroscopy at comparable reaction conditions. A lower rate of methylation per Brønsted acid site is seen for H-beta, and this is linked to the formation of fairly persistent cationic species, as observed with FT-IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…By performing extraction on the spent catalyst samples at the end of each experiment, we confirmed that the only retained species are monocyclic aromatics ranging from xylenes to hexaMB in all the catalyst. This observation together with the observations of the dynamic of FTIR bands and the literature [69][70][71][72][73][74][75] lead us to make the following band assignation: the C=C or C-H in-plane stretching vibration in the aromatic rings of alkylbenzenes (1591 and 1616 cm -1 ), the joint contribution of polycyclic aromatics and alkylbenzenes (1456 and 1570 cm -1 ) and polycyclic aromatics (1480 cm -1 ). Bauschlicher et al [76] associated the 1480 cm -1 band to the C-H in-plane vibration in polycyclic aromatics, and this band displaces toward higher wavenumber and increases in intensity as the molecule becomes larger.…”
Section: Ftir Operando Reactormentioning
confidence: 57%
“…By performing extraction on the spent catalyst samples at the end of each experiment, we confirmed that the only retained species are monocyclic aromatics ranging from xylenes to hexaMB in all the catalyst. This observation together with the observations of the dynamic of FTIR bands and the literature [69][70][71][72][73][74][75] lead us to make the following band assignation: the C=C or C-H in-plane stretching vibration in the aromatic rings of alkylbenzenes (1591 and 1616 cm -1 ), the joint contribution of polycyclic aromatics and alkylbenzenes (1456 and 1570 cm -1 ) and polycyclic aromatics (1480 cm -1 ). Bauschlicher et al [76] associated the 1480 cm -1 band to the C-H in-plane vibration in polycyclic aromatics, and this band displaces toward higher wavenumber and increases in intensity as the molecule becomes larger.…”
Section: Ftir Operando Reactormentioning
confidence: 57%
“…In the concerted mechanism, MeOH reacts directly with the hydrocarbon in a single step to form a methylated product and H 2 O; thus, protonation and C–C bond formation occur simultaneously in one step, and an intermediate is not required, as the reaction proceeds via coupling of adsorbed methanol on the BAS with the species that is being methylated . The initial step starts with the physisorption of a methanol molecule on the BAS of the zeolite (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…As far as the mechanism of the zeolite-catalyzed methylation reaction is concerned, two different proposals have been advocated in literature: a stepwise route that involves a surface-bound methoxy group intermediate, and a concerted mechanism in which physisorbed methanol directly interacts with the species to be methylated. ,, In this work only the concerted mechanism is considered, since experimental kinetic measurements are explained by this mechanism. , The confinement effect of different zeolite cavities (H-ZSM-5 and H-Beta) are evaluated assuming the same mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several negative bands at 3740, 3670 and 3601 cm -1 were observed. The bands at 3740 cm −1 and 3670 cm −1 may be assigned to Si-OH and Al-OH vibrations located at the extra framework of zeolites or the external surfaces of microcrystals, respectively, whereas the weak negative band at 3601 cm −1 is due to the stretching vibrations of bridging OH group Al–(OH)–Si 34 , 37 39 . Compared with H-ZSM-5-100, the negligible 1474 cm −1 band for H-ZSM-5-25 disappeared after He purging, suggesting the substitution of H + by K + .…”
Section: Discussionmentioning
confidence: 99%